Peningkatan Fungsi Daun Chaya sebagai Agen Reduksi pada Sintesis Seng Nanopartikel - sri wahyu suciayti; Suprihatin Suprihatin; Fegi Liani; Posman Manurung (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Nano-ZnO biosynthesis has been carried out using Chaya leaves with the addition of 0.7M NaOH. The aim is to determine the results of nano-ZnO synthesis regarding the formation of functional groups, phase structure, morphology, band gap energy, and its potential as an antibacterial. The synthesis process was carried out in three stages, namely, extraction of Japanese papaya leaves, synthesis of nano-ZnO, and characterization using Fourier Transform Infra Red (FTIR), X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM), and UV-Diffuse Reflectance (UV-DRS). Nano-ZnO samples were applied in antibacterial tests. The results of FTIR analysis show the formation of ZnO functional groups at wave numbers 599-509 cm-1 with the main functional groups involved being O-H, C=O, N-H, and C-N. The results of the XRD analysis showed that the phases formed in the sample were zinc oxide, zinc phosphate, zinc iron oxide and zinc chlorate hydrate. Factors that influence the formation of other phases are because Japanese papaya leaves contain phosphorus and iron, the ZnO phase formed has a wurtzite structure. The results of UV-DRS analysis show that the band gap energy is close to the standard of 3.24 eV with an absorbance value of 362 nm. TEM results show that the particle morphology experiences agglomeration due to the presence of other compounds. The antibacterial activity of Nano-ZnO with a NaOH concentration of 0.7 M resulted in an average zone of inhibition of bacterial growth in E.coli of 0.21 mm.